Compatibility of Semantics of Suffixes with Gender Assignment in Old English - Soloviova, Olga; Bloshchynskyi, Ihor; Tsviak, Larysa; Voitiuk, Olena; Mysechko, Olha (My University, 2021)
The article reveals the research results of a correlation between principles of gender assignment and meaning of coined words. In Old English, derivatives belonging to three genders (masculine, feminine and neuter), inherited from Proto-Indo-European legacy, were numerous and their suffixes were determined to some extent on the basis of semantic criteria. Our research aimed at investigating the possibility of a connection between genders of suffixes and the semantic peculiarities of their derivatives. To carry the analysis and identify the meaning of suffixes, we set 21 semantic groups which were characteristic of Old English derivatives. The findings suggest that there are certain semantic regularities that are part of the gender assignment system in Old English. The majority of masculine and feminine suffixes are responsible for nouns belonging to 3 – 5 semantic groups while the neuter suffixes have from 2 to 4 semantic groups. Thus, it is possible to divide suffixes according to their primary semantic content. The paper provided evidence that derivatives of each gender have the following semantic segments: notions of people, administration and social stratification for masculine suffixes; abstractions, feelings and emotions, traits of character and activities for feminine ones, and structures, locations and lifeless objects for neuter suffixes. It was also evident that semantic peculiarities of Old English suffixes build a ground for the competition between them and are vital for their further development in an English language course.
Keywords: Coinage productivity; Gender assignment; Semantic groups; Semantic motivation; Semantic restrictions